Land Acquisition in Afghanistan : A Report - McAuslan, Patrick (World Bank, Washington, DC, 2012)
The purpose of this report is to review and assess Afghanistan's legal framework regulating social safeguards (national and local laws, regulations, procedures and policies) with special reference to the law and practice of compulsory land acquisition, or expropriation. The overall objective of the report is to consider how Afghanistan's legal framework would address social safeguard issues in upcoming World Bank projects which are likely to involve land acquisition and resettlement of those persons whose land is to be acquired in connection with project implementation. The report will consist of a narrative of the context within which the assessment will be conducted and the assessment which will in both narrative and tabular form. Afghanistan is embarking upon a massive programme of public works to improve and upgrade the infrastructure of the country: better roads, clean water; more schools and hospitals in both rural and urban areas are needed to provide a better life for all Afghans. The World Bank is committed to providing assistance towards the realization of this programme. Much of these public works will involve the acquisition of land on which people are at present living and obtaining a livelihood from. It is important to stress at the outset of this report that far from the object of the report being to impede or prevent these necessary public works, the aim of the report and any consequential changes in the law which might result from its proposals are designed to facilitate those public works by providing for a clear and fair system of land acquisition, compensation and resettlement for those people who will be required to leave their homes and land for the greater public good in order that the public works can be carried out. Where people are satisfied that they have been treated fairly, they will be more likely to co-operate in being moved from their homes and this will facilitate the execution of the public works.